Absolute distance measurement in water by optical comb for in-process meaurement of water-guided laser processing. (December 2021) - Masuda, Shusei; Kadoya, Shotaro; Michihata, Masaki; Takahashi, Satoru
Abstract: Water-guided laser processing have been widely used because of low heat affected zone and high aspect ratio processing. However, its processing point is not determined and must be measured with several μm accuracy. For this purpose, in-process measurement method was proposed. Measurement beam of optical comb is coaxially introduced to processing beam so that absolute distance of optical path in water-guide is measured with using optical comb tandem pulsed interferometer in water. To verify the principle of proposed method, in-water absolute distance measurement was evaluated. Repeatability of in-water measurement was under 100 nm and 1.0 mm displacement of target mirror in water was properly measured with under 1 μm error from reference displacement sensor. From these results, it is confirmed that proposed method properly works in-water environment.